In search of more than a state: trajectories of political ordering and identity plurality in Somalia. Issue 2 (3rd April 2017) - Balthasar, Dominik
Abstract: Past and present efforts at reconstructing a Somali state have centred on the long-standing claim that Somalis have constituted a 'nation in search of a state'. Yet, casting Somali state trajectories in a historical light, this article shows that the Somali sociopolitical construct has always been much less homogenous and united than frequently depicted. Analysing Somali state-making endeavours from the final years of colonialism in the late 1950s to the politico-territorial fragmentation of the 1990s, I argue that Somalis have not only been in search of a state, but Somali society has been characterized by the emergence of plural political identities, inhibiting the consolidation of a national identity. I propose that the identity plurality has largely hinged on the volatility and multiplicity of institutions broadcasted in the context of changing politico-territorial orders. The article suggests that political identity in Somalia has been dynamic and fluctuating during the post-independence decades, that it hinged significantly on aspects of territorial ordering and concomitant institutional structures, and that the formation of a cohesive Somali national identity has in part been hampered by the governments' inability to build and implement overarching political institutions. This carries important implications for contemporary efforts at addressing conflict and fragility in Somalia. Federalization and mini-state formation are likely to see regional identities trump its national counterpart. Yet, it might also spark a process in which political identities start overriding kinship ones, which has been a shared central policy objective of many governments of the past.